2018
DOI: 10.1111/all.13687
|View full text |Cite
|
Sign up to set email alerts
|

Chemically modified peanut extract shows increased safety while maintaining immunogenicity

Abstract: Background: Peanuts are most responsible for food-induced anaphylaxis in adults in developed countries. An effective and safe immunotherapy is urgently needed. The aim of this study was to investigate the immunogenicity, allergenicity, and immunotherapeutic efficacy of a well-characterized chemically modified peanut extract (MPE) adsorbed to Al(OH) 3 . Methods: Peanut extract (PE) was modified by reduction and alkylation. Using sera of peanut-allergic patients, competitive IgE-binding assays and mediator relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…It has been reported that after specific treatment, some food allergens will lose the IgE‐induction ability (allergenicity) but maintain the IgE‐ and T cell‐induction capacity (immunogenicity) and, therefore, can be used as hypoallergens for immunotherapy. [ 65,66 ] Here, we demonstrated that LcZ led to similar responses through the suppression of IgE, the maintenance of IgG, and the promotion of IgA, as well as the activation of a series of immune cells. Consequently, LcZ is a potential immunomodulator that may be applied to facilitate immunotherapy.…”
Section: Discussionmentioning
confidence: 85%
“…It has been reported that after specific treatment, some food allergens will lose the IgE‐induction ability (allergenicity) but maintain the IgE‐ and T cell‐induction capacity (immunogenicity) and, therefore, can be used as hypoallergens for immunotherapy. [ 65,66 ] Here, we demonstrated that LcZ led to similar responses through the suppression of IgE, the maintenance of IgG, and the promotion of IgA, as well as the activation of a series of immune cells. Consequently, LcZ is a potential immunomodulator that may be applied to facilitate immunotherapy.…”
Section: Discussionmentioning
confidence: 85%
“…Different adjuvants are currently used as a booster for the OVA model, mostly for the establishment of food allergies 79 . The most frequently used are cholera toxin (CT), 91 staphylococcus enterotoxin B (SEB), 90 aluminium hydroxide 90 and lipopolysaccharide (LPS) 89 . The use of cholera toxin as an adjuvant efficiently induces allergen‐specific Th2 responses.…”
Section: Currently Available “Ad” Animal Modelsmentioning
confidence: 99%
“…The major issues in treating food allergy by immunotherapy are safety, the low rate of tolerance induction, a high rate of side effects and dropouts, a lack of understanding of the optimal dose and time of treatment, and the existence of only few, suboptimal biomarkers that predict treatment response and how to perform multifood OIT . These limitations are addressed in numerous treatment approaches: (a) peptide immunotherapy targeting the T‐cell compartment and lacking IgE cross‐linking; (b) hypoallergenic variants of allergens or extracts by chemical or thermal modification or mutations which combine reduced desensitization with a minimally altered T‐cell epitope diversity; (c) the usage of immunomodulatory substances and/or particles; (d) the addition of prebiotics and/or probiotics; (e) the application of biologics either alone or as adjuvants of OIT; (g) very low dose OIT; and (h) sublingual OIT.…”
Section: Unmet Needs and Future Research Areas In Treatment Of Allergmentioning
confidence: 99%